Environmental Sustainability and Improved Quality of Life Through Service Convergence Technologies - Aboudi, Meisam; Talevski, Alex (IEEE Computer Society, 2010)
This paper proposes the use of a wireless sensor network system as applied in a Smart Mining Camp to remotely control amenity functions and reduce energy consumption / emissions. Furthermore, we investigate such environmental sustainability and improved quality of life aspects through the use of multimedia convergence technologies.